Power Grid Analyzer, Part I—Power Flow and Optimal Power Flow - Sorasak Jaingeawkum; Suphanat Sodsa-Ard; Thirawit Chansiri; Voraya Suwannachote; Tossaporn Surinkaew; Teeraphon Phophongviwat; Issarachai Ngamroo (My University, 2025)
In this paper, we introduce Power Grid Analyzer (PGAz), an open-source software package based on MATLAB, specifically designed for analyzing and controlling future power grids. Initially, PGAz is equipped with four fundamental features: power flow (PF), optimal power flow (OPF), small-signal stability analysis (SSSA), and time-domain simulation (TS). At this stage, Part I concentrates on the development of PF and OPF. The formats of our developed tool are presented, along with its command prompts. In this part, we have developed several conventional yet effective methods in the PGAz package to address PF and OPF problems, including techniques such as the Newton-Raphson method, Gauss-Seidel method, Interior Point Method, Iwamoto’s method, Fast Decoupled Load Flow, Genetic Algorithm, and Particle Swarm Optimization. Additionally, it em-phasizes important aspects, algorithms, and various case studies that have been tested against IEEE benchmarks ranging from the IEEE 5-bus to the IEEE 300-bus test systems. The results demonstrate the capabilities of PGAz for future educational and research applications in PF and OPF. Finally, we outline a plan for developing Part II, which will mainly focus on SSSA and TS.
Keywords: Power Quality and Harmonics; Power System Optimization and Stability; Energy Load and Power Forecasting